The Effect of Reading Aloud on Pronunciation and Comprehension in EFL Learners - Ibrohimova Muxtasarxon Masumxon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This study explores the impact of reading aloud on the development of pronunciation and reading comprehension skills among learners of English as a Foreign Language (EFL). Reading aloud, a traditional yet often overlooked technique, engages multiple cognitive and sensory channels, reinforcing phonological awareness and improving oral fluency. This paper analyzes how regular guided reading aloud sessions contribute to more accurate pronunciation, intonation, and stress patterns. It also investigates the extent to which reading aloud enhances comprehension by encouraging active engagement with the text. Through a review of relevant literature and classroom based observations, the study argues that reading aloud is a valuable tool for both linguistic and cognitive development in EFL classrooms.